Solid Organ Donation and Transplantation in the United Kingdom: Good Governance is Key to Success - Johnston-Webber, Charlotte; Mah, Jasmine; Prionas, Apostolos; Streit, Simon; Wharton, George; Forsythe, John; Mossialos, Elias; Papalois, Vassilios (Transplant International, 2023)
The United Kingdom (UK) supports a highly successful organ donation and transplantation program. While the UK originally had one of the lowest organ donation rates in Europe, sustained reforms have resulted in steady improvement. Of note, the UK nearly doubled its rate of deceased donations between 2008 and 2018. In this report, we present a case study of the UK organ donation and transplantation program as an example of a complete system with sound and inclusive governing structures that are strongly integrated with critical programs focused on training and research. This study was based on an initial targeted review of the literature led by a UK expert that included guidelines, national reports, and academic papers. Feedback solicited from other European experts was incorporated into our findings via an iterative process. Overall, the study highlights the step-wise evolution of the UK program that ultimately became successful largely due to ongoing collaborative efforts carried out at all levels. Centralized coordination of all aspects of the program remains a key driver of improved rates of organ donation and transplantation. The designation and empowerment of expert clinical leadership have helped to maintain focus and promote ongoing quality improvement.